Preparation and characterization of poly(vinyl alcohol)/sodium alginate hydrogel with high toughness and electric conductivity. (15th April 2018) - Jiang, Xiancai; Xiang, Nanping; Zhang, Hongxiang; Sun, Yujun; Lin, Zhen; Hou, Linxi
Highlights: The PVA/SA hydrogels were prepared by freezing/thawing process and soaking in NaCl aqueous solution. The chain entanglement between PVA and SA macromolecular chains increased due to the salting-out effect. The PVA/SA hydrogel with tensile strength of 1.32 MPa, elongation at break of 400% and conductivity of 3.62 S/m were obtained. Abstract: Development of bio-based hydrogels with good mechanical properties and high electrical conductivity is of great importance for their excellent biocompatibility and biodegradability. Novel electrically conducive and tough poly(vinyl alcohol)/sodium alginate (PVA/SA) composite hydrogel was obtained by a simple method in this paper. PVA and SA were firstly dissolved in distilled water to form the composite solution and the pure PVA/SA hydrogel was obtained through the freezing/thawing process. The pure PVA/SA hydrogels were subsequently immersed into the saturated NaCl aqueous solution to increase the gel strength and conductivity. The effect of the immersing time on the thermal and mechanical properties of PVA/SA hydrogel was studied. The swelling properties and the antiseptic properties of the obtained PVA/SA hydrogel were also studied. This paper provided a novel way for the preparation of tough hydrogel electrolyte.